Détournements et viralité dans la campagne présidentielle de Marine Le Pen de 2022 - Alida Maria Silletti (MediAzioni)
This research examines 2022 Marine Le Pen’s presidential campaign on the web, namely via her Twitter profile « SansLui », coming from Emmanuel Macron’s slogan « Avec vous ». Attention will be paid to strategies and techno-discursive tools used in order to create a viral campaign, by looking at three discursive productions which appear as the iconographic part of the tweets inside « SansLui » profile: posters, gifs and messages by her electorship. « Sans lui » will be analysed as a counter-slogan which becomes a formulaic sentence whose productivity, but also isolation and fragmentation, are encouraged by Twitter itself. Methodology will be based on French Discourse Analysis as far as formulaic sentences, Twitter discursive productions, digital discourse, populist discourse and hate speech discourse are concerned. This study will show that « SansLui » Twitter profile deals with an intrinsic virality thanks to its technodiscursive tools but also to the way its tweets have been conceived. It also confirms that this Twitter profile is a way for Marine Le Pen for stressing disapproval against Emmanuel Macron’s action by inspiring negative feelings such as deception, anger, and hate, and, as a consequence, for reinforcing her ethos.